2008
DOI: 10.1113/jphysiol.2007.145722
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐mediated dilatation in the superficial femoral artery is nitric oxide mediated in humans

Abstract: Flow-mediated dilatation (FMD) of the brachial and radial arteries is an important research tool for assessment of endothelial function in vivo, and is nitric oxide (NO) dependent. The leg skeletal muscle vascular bed is an important territory for studies in exercise physiology. However, the role of endothelial NO in the FMD response of lower limb arteries has never been investigated. The purpose of this study was to examine the contribution of NO to FMD in the superficial femoral artery in healthy subjects. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
153
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(159 citation statements)
references
References 39 publications
5
153
0
1
Order By: Relevance
“…Previous studies have shown that both aged individuals and individuals with PAD show a lower blood flow response to passive movement suggesting impaired NO function [5,6]. Similarly, reactive hyperaemia, which is also highly dependent on NO [7,8], is lower in the aged and in PAD compared to young healthy individuals [9]. This raises questions about the control of blood flow in PAD and presents the possibility that in addition to arterial stenosis, altered NO availability, and thereby limited vasodilation, might contribute to the impairment in leg blood flow of PAD patients during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that both aged individuals and individuals with PAD show a lower blood flow response to passive movement suggesting impaired NO function [5,6]. Similarly, reactive hyperaemia, which is also highly dependent on NO [7,8], is lower in the aged and in PAD compared to young healthy individuals [9]. This raises questions about the control of blood flow in PAD and presents the possibility that in addition to arterial stenosis, altered NO availability, and thereby limited vasodilation, might contribute to the impairment in leg blood flow of PAD patients during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used method to assess endothelial function in humans is flow-mediated dilatation (FMD), which measures the ability of the blood vessels to accommodate increases in flow by altering their internal diameter, and is dependent on nitric oxide (NO) release by endothelial cells. 62 Several studies document a direct independent relationship between the risk for cardiovascular events and the degree of brachial FMD in non-SCI individuals, [63][64][65] whereby the degree of cardiovascular risk is increased as the degree of brachial FMD is reduced.…”
Section: Conduit Arterial Function After Sci Structural Adaptationsmentioning
confidence: 99%
“…68 In the SFA, individuals with SCI exhibit an increased absolute FMD compared with AB individuals; 69 however, this difference is no longer present when the degree of FMD is corrected for area under the shear rate curve, from the time of occluding cuff deflation to that of peak diameter attainment. 62 Such correction for the eliciting shear stress stimulus on the endothelial cell membrane is considered critical, especially in cases where arteries are compared with different baseline diameters (for example, SCI vs control). 61 In the only study to investigate brachial artery FMD, it was reported that absolute brachial artery FMD is not different between SCI and AB individuals, whereas brachial artery FMD expressed relative to the shear rate stimulus (in this case the change in shear rate ratio from rest to peak hyperemic response) was reduced in SCI compared with AB.…”
Section: Conduit Arterial Function After Sci Structural Adaptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide (NO) is a lipid soluble gas implicated in a wide array of biological functions such as vascular function (Kooijman et al, 2008), capillarization (Gavin, 2009), blood flow regulation (Radegran & Saltin, 1999), muscle contractile function (Kobzik et al, 1994) and cell signalling (Steensberg et al, 2007). NO is synthesised enzymatically by three recognised NO synthase (NOS) isoforms termed; neuronal NOS (nNOS), endothelial NOS (eNOS) and inducible NOS (iNOS), with nNOS being the primary isoform in the skeletal muscle (Frandsen et al, 1996;Rudnick et al, 2004).…”
Section: Nitric Oxidementioning
confidence: 99%